Adjudication of electoral competition in Dominican Republic and Brazil: two different paths - Nogueira, Ary Jorge Aguiar (Estudos Eleitorais, 2025)
Elections constitute one of the fundamental elements of contemporary democracies. While there exists a robust body of scholarship on electoral governance, significant opportunities for research remain, particularly in the adjudication of results. This study focuses on the adjudication of electoral competition in the Dominican Republic and Brazil, addressing the following question: how has the adjudication of elections varied over time in these countries? To this end, the study draws upon relevant literature on institutional change and seminal works in electoral governance. The work is primarily descriptive, comparing the institutions without losing sight of the historical neoinstitutionalist perspective. Methodologically, a small-N analysis was selected. Although this approach has limitations in terms of causal inference, it enables more detailed studies that provide a deeper understanding of the phenomenon being analyzed. In addition to reviewing pertinent literature, empirical data were used, partly collected previously and partly collected for this purpose. Temporally, the study focuses on the 2020 elections held in both countries. The results suggest that, although there are similarities in the models of electoral governance adopted in the two countries, significant differences exist in the scope of adjudication, especially regarding levels of regulation and specialization. The Dominican Republic exhibits a lower regulatory volume compared to Brazil. Additionally, it has a specialized Superior Electoral Court dedicated to adjudication, whereas its Brazilian counterpart is responsible for the entire electoral governance system.